Dictionary of the English language 2026-02-12T05:51:51+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Johnson, Samuel, 1709-1784 (Arno Press, 1979)

(untitled)
A dictionary with more than 40,000 entries which was a primary reference source for scholars and writers of the 18th and 19th century